Carcass and meat quality of broiler chickens reared on herb residues - K. Lokaewmanee; R. Sirival (Diponegoro University, 2022)
This study was conducted to determine the effects of herb residues on carcass and meat quality in broilers. A total of 160 chicks were divided into four groups, each with four replicates of 10 chicks; the chicks were provided ad libitum access to a control diet or the same diet supplemented with Zingiber cassumunar, Kaempferia galangal, or Curcuma aromatica residues at 0.3% feed. At 42 days of age, 20 chicks from each group were slaughtered, and the carcass and meat quality were determined. All exper-imental groups demonstrated lower abdominal fat weight, and the K. galangal group had a significantly higher total visceral organ weight than that of the control group (P<0.05). The experimental groups demonstrated improved color of the breast muscle, breast fillet muscle, skin, and abdominal fat (P<0.05). The shear force value of the breast muscle increased in the K. galangal group, whereas that of the thigh muscle increased in all experimental groups (P< 0.05). The highest overall acceptability of raw and cooked chicken breast meat was produced by 0.3% C. aromatica residue supplementation (P<0.05). These finding suggest that the inclusion of 0.3% C. aromatica residue in the diets resulted in improved overall acceptability of breast meat without negatively affecting dressing percentage.